ҚАРАҚАЛПАҚ ТИЛИНДЕ КИЙИМ-КЕНШЕК АТАМАЛАРЫНЫҢ ЖАСАЛЫЎ усыллары - Зайрова, Қ. (FAN va JAMIYAT, 2025)
This article talks about the ways of forming the names of clothing items in the Karakalpak language. The analysis of materials related to the names of clothing items is carried out, the methods of forming these names are shown, such as the lexico-semantic method, the method of affixation, as well as complex words. It was found that new words formed in a lexico-semantic way appeared as a result of changes in the semantics of already existing words.